Isolation and Characterisation of Lutein from Commelina Benghalensis L. Leaves and Its Sun Protection Factor Activity - A. Krishnaveni (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Back ground Objective To isolate the lutein from Commelinabenghalensis L. and its sun protection factor determination Methods Lutein was isolated by diethyl ether and methanol followed by saponification process. Isolated compound was identified by using UV, NMR and GC-MS spectral analysis. Sun Protection Factor determined by using spectrophotometer. Readings were taken in wavelength ranging from 290 to 320 at 5nm interval and readings were noted down. SPF for isolated lutein can be calculated by applying the formula known as Mansur equation. Results The isolated compound shows absorbance maxima at 470, 444 nm it indicate the presence of lutein. UV, NMR, GC-MS studies confirmed the isolated compound is lutein.The SPF number of lutein 50?g/ml is 1.15 ± 0.43. The SPF number of lutein 100?g/ml is 2.38 ± 0.90. The SPF number of lutein 200?g/ml is 4.75 ± 1.79. SPF value for sunscreen above 2 is considered as having good sunscreen activity. Marketed sunscreen lotion having concentration 200 ?g/ml shows SPF value about 0.66±0.006 whereas lutein showed hogh sun protection factor. Conclusion Isolated compound lutein possessing good sun screen activity. Recommendation Herbal formulations can be prepared and evaluated further with other sensitivity tests